Asociatividad artesanal y desarrollo turístico en la comunidad el chino de la reserva comunal Tamshiyacu Tahuayo 2024 - Arevalo Shapiama, Gustavo (2025)
The objective of this research was to determine the relationship between artisan associations and tourism development in the El Chino Community of the Tamshiyacu Tahuayo 2024 Communal Reserve. A basic type of research was carried out, at a descriptive-correlational level, and with a non experimental design. The population studied included 60 families residing in the El Chino Community, who played a crucial role in the development of the research. For data collection, the survey technique through questionnaires was used. The results indicated that artisan associations in the community are considered regular, with 30% of respondents stating that the constant collaboration between artisans facilitates the opening of new markets for their products. Regarding tourism development, 32% of respondents rated it as regular, attributing this perception to the occasional participation of community members in tourism activities. In general terms, a low positive correlation was found between craft associativity and tourism development, reflected in a Spearman coefficient of 0.493, with a statistical significance of 0.002